2023
DOI: 10.1044/2022_persp-22-00074
|View full text |Cite
|
Sign up to set email alerts
|

Clinician Perspectives of Telehealth Pre–COVID-19: A Systematic Review and Qualitative Metasynthesis

Abstract: Purpose: The purpose of this study was to describe clinicians' attitudes and beliefs about telehealth prior to the COVID-19 pandemic and establish a baseline measure for change. Method: This study is a qualitative systematic review and metasynthesis, using the Enhanced Transparency in Reporting the Synthesis of Qualitative Research guideline. Seven databases were searched. Studies were included if they used interviews or focus groups, included at least … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…However, the evidence is not unequivocal. On the contrary, other studies have demonstrated a lack of impact of telerehabilitation for individuals with aphasia in a functional capacity (Woolf et al, 2016) and have signalled reservations and concerns from professionals involved in its delivery (Douglass et al, 2023). Telehealth is also impeded by practical issues such as poor audio or visual quality, availability of equipment and connectivity as well as virtual communication being simply less favoured than face-to-face communication (Shahouzaie & Gholamiyan Arefi, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, the evidence is not unequivocal. On the contrary, other studies have demonstrated a lack of impact of telerehabilitation for individuals with aphasia in a functional capacity (Woolf et al, 2016) and have signalled reservations and concerns from professionals involved in its delivery (Douglass et al, 2023). Telehealth is also impeded by practical issues such as poor audio or visual quality, availability of equipment and connectivity as well as virtual communication being simply less favoured than face-to-face communication (Shahouzaie & Gholamiyan Arefi, 2022).…”
Section: Introductionmentioning
confidence: 99%